Generational Transformation and Its Reflection on Project Success: The Gen-Z - Oezen, Ali Ersen; Demirdogen, Goekhan; Demirbag, Alperen Taha; Aladag, Hande; Isik, Zeynep (TURKISH CHAMBER CIVIL ENGINEERS, 2024)
Nowadays, Gen-Z members with a high ability to use high-tech products have just entered the labor market to take responsibility in construction projects. Gen-Z members must work together with other generations and different work styles. If the harmonization among generations is not managed properly, it will decrease the productivity of the construction industry. Therefore, this study aims to identify the Gen-Z characteristics and their impacts on the project success by using Structural Equation Modeling (SEM) method. SEM results showed that Gen-Z characteristics contribute to project success through communication. Therefore, communication-related practices must be overviewed and rearranged according to Gen-Z requirements. The findings will contribute to the in-company employee strategies and assist in adapting Gen-Z members into the construction industry to increase productivity
Keywords: Construction industry; generation Z; innovation; performance managemen; human resource management; STRUCTURAL EQUATION MODELS; MANAGEMENT; Engineering